Psychometric study of a measurement scale for the teaching of social skills to students with special educational needs - KEFALA, GEORGIA (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Teaching social skills to students with special educational needs is essential for their personal development and integration into society. Objectives. The purpose of this study is to validate a measurement instrument for the elements involved in teaching and learning social skills in students with special educational needs. Two studies were conducted to accomplish this objective. Methods. Firstly, an exploratory study, with half of the sample, consisting a sample of 166 Greek teachers working in primary and secondary schools of special and general education, in Western Macedonia region. Secondly, a confirmatory study, consisting of a sample of 185 Greek teachers who also work in primary and secondary schools of special and general education in the same region. All education professionals work with students with mild special educational needs. The instrument used was an “ad hoc” created questionnaire, consisting 17 items of a 5 point the Likert scale, to which different analyses were applied to verify its validity and reliability. Results. An Exploratory Factor Analysis (EFA) showed a total of 3 factors corresponding to the “Preparedness of Teachers in Teaching Social Skills”, to the “Elements of Influence on Teachers' Suitability in Teaching Social Skills” and to the “Elements that play an important role in Teaching Social Skills”. Subsequently, a Confirmatory Factor Analysis (CFA) was carried out, through which the results derived from the AFE were ratified. Conclusion. The findings reveal an instrument that is adequate in validity and reliability, in accordance with the literature, demonstrating that the model is consistent and coherent with the initial theoretical assumptions.
Keywords: special education, teachers’ preparedness, teaching social skills, EFA, CFA